Simple and Efficient AlN-Based Piezoelectric Energy Harvesters - Gablech, Imrich; Klempa, Jaroslav; Pekárek, Jan; Vyroubal, Petr; Hrabina, Jan; Holá, Miroslava; Kunz, Jan; Brodský, Jan; Neužil, Pavel (Micromachines, 2020)
In this work, we demonstrate the simple fabrication process of AlN-based piezoelectric energy harvesters (PEH), which are made of cantilevers consisting of a multilayer ion beam-assisted deposition. The preferentially (001) orientated AlN thin films possess exceptionally high piezoelectric coefficients d33 of (7.33 ± 0.08) pC∙N-1. The fabrication of PEH was completed using just three lithography steps, conventional silicon substrate with full control of the cantilever thickness, in addition to the thickness of the proof mass. As the AlN deposition was conducted at a temperature of ≈330 °C, the process can be implemented into standard complementary metal oxide semiconductor (CMOS) technology, as well as the CMOS wafer post-processing. The PEH cantilever deflection and efficiency were characterized using both laser interferometry, and a vibration shaker, respectively. This technology could become a core feature for future CMOS-based energy harvesters.
Keywords: micro-electro-mechanical systems (MEMS) cantilever; high performance; AlN; energy harvesting; complementary metal oxide semiconductor (CMOS) compatible